Parental involvement in school-based mental health interventions for young people in low-resource settings: A qualitative study from Zimbabwe and Ghana - Rufaro Hamish Mushonga; Rebecca Jopling; Franklin Glozah; Tiny Tinashe Kamvura; Suzanne Dodd; Denford Gudyanga; Arnold Maramba; Edith Dambayi; Christopher Abio Ayuure; Tarisai Bere; Fabian Sebastian Achana; Lucy Owusu; et al. (PLoS ONE, 2025)
Background Young people in low-resource settings are disproportionately affected by mental health problems, yet access to formal mental healthcare remains limited. However, schools in these regions have increasingly become the primary settings for mental health interventions, offering an accessible and supportive environment for mental health services. Recognising the critical role schools play in providing mental health services for young people, there has been a growing emphasis on involving parents in school-based mental health (SBMH) interventions in low-resource settings. This study explored the mechanisms for effectively involving parents in SBMH interventions for young people in Zimbabwe and Ghana. Methods Cross-sectional qualitative research was conducted in Harare, Zimbabwe and Navrongo, Ghana. This study is a sub-analysis of a larger formative qualitative study which aimed to identify evidence for adapting interventions for depression and anxiety for young people aged 15–24 in Zimbabwe, and 15–18 in Ghana, and test the feasibility of the adapted intervention. We utilised semi-structured in-depth interviews, key informant interviews and focus group discussions with various stakeholders until data saturation was achieved. All interviews were audiotaped and later transcribed verbatim and translated to English for analysis. Data for this study were inductively coded and analysed using thematic analysis. Results Effective mechanisms for engaging parents in SBMH include routine parent-teacher meetings, interface meetings between parents and school-based mental healthcare providers, and direct parental participation in sessions. However, while parental involvement is key for SBMH interventions, it can be problematic. In some cases, parents may unintentionally breach their children’s privacy and confidentiality or may be the source of their children’s mental health problems. Conclusion The study’s findings underscore the importance of parents as vital partners in SBMH interventions. Given the positive impact of parental involvement, it is essential to incorporate parents into the design and implementation of these interventions. By leveraging the insights from this study, interventionists can develop and implement more effective and low-cost SBMH interventions, which can significantly improve mental health outcomes for young people in low-resource settings.